Hope and otherness : Christian eschatology and interreligious hospitality - Wirén, Jakob. (Currents of Encounter, 2018)
In Hope and Otherness , Jakob Wirén analyses the place and role of the religious Other in contemporary eschatology. In connection with this theme, he examines and compares different levels of inclusion and exclusion in Christian, Muslim, and Jewish eschatologies. He argues that a distinction should be made in approaches to this issue between soteriological openness and eschatological openness. By going beyond Christian theology and also looking to Muslim and Jewish sources and by combining the question of the religious Other with eschatology, Wirén explores ways of articulating Christian eschatology in light of religious otherness, and provides a new and vital slant to the threefold paradigm of exclusivism, inclusivism and pluralism that has been prevalent in the theology of religions. "Jakob Wirén's study pushes forward the frontiers of three disciplines all at the same time: theology of religions; comparative religions and eschatology. (...) This is a challenging and important book." - Gavin D'Costa, University of Bristol, Professor of Catholic Theology, 2017 "This book explores of the status of religious others in Christian eschatology, and of eschatology itself as a privileged place for reflecting on religious otherness. Wiren mines not only Christian, but also Jewish and Muslim sources to develop an inclusive eschatology. Hope and Otherness thus represents an important contribution to both theology of religions and comparative theology." - Catherine Cornille, Boston College, Professor of Comparative Theology, 2017